2021
DOI: 10.1101/2021.04.26.441523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomics Sheds Light on the population structure ofMycobacterium bovisfrom a Multi-Host Tuberculosis System

Abstract: Molecular analyses of Mycobacterium bovis based on spoligotyping and Variable Number Tandem Repeat (MIRU-VNTR) brought insights into the epidemiology of animal tuberculosis (TB) in Portugal, showing high genotypic diversity of circulating strains that mostly cluster within the European 2 clonal complex. The genetic relatedness of M. bovis isolates from cattle and wildlife have also suggested sustained transmission within this multi-host system. However, while previous surveillance highlighted prevalent genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our results showed that this cannot be conducted for areas with high diversity such as the one we considered, as we observed little correspondence between the MCC tree branches and the spoligotypes. Similarly, other studies pointed out the limitations of such typing techniques ( 18 ), in the case of an expanding infection where transmission is steadily ongoing, compared with point-source ones ( 74 ). The high SNP distances among the sampled isolates also precluded the use of methods to infer direct transmission between hosts ( 7 , 75 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results showed that this cannot be conducted for areas with high diversity such as the one we considered, as we observed little correspondence between the MCC tree branches and the spoligotypes. Similarly, other studies pointed out the limitations of such typing techniques ( 18 ), in the case of an expanding infection where transmission is steadily ongoing, compared with point-source ones ( 74 ). The high SNP distances among the sampled isolates also precluded the use of methods to infer direct transmission between hosts ( 7 , 75 ).…”
Section: Discussionmentioning
confidence: 96%
“…These are spoligotyping and MIRU-VNTR typing as follows: the former is based on the presence of multiple spacer oligonucleotides in the genome direct repeat region, while the latter is based on 12 loci containing variable numbers of tandem repeats of mycobacterial interspersed repetitive units ( 16 , 17 ). Compared with WGS, these techniques consider a limited genome region and can be more subject to homoplasy ( 18 ). The results reported by Egbe ( 15 ) showed that most of the isolates belonged to the Af1 clonal complex ( n = 250/total n = 255), while the remaining ones had an unidentified clonal complex.…”
Section: Introductionmentioning
confidence: 99%